PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TERINDEX LQ45 PERIODE TAHUN 2018-2021 (JAPB, 2022)
This study aims to examine the effect of financial performance on firm value as measured by ratios/financial indicators. This type of research is quantitative research using manufacturing financial reports listed on the Indonesian Stock Exchange. Furthermore, the data collection method used is a purposive sampling approach and IDX LQ45 based on manufacturing company criteria, listing for 4 consecutive years in the 2018-2021 period. Processing techniques and data analysis were carried out using multiple linear test equipment through the GesCA analysis test. Based on the research results, it can be concluded that financial performance has an effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange. The magnitude of the influence of the financial performance variable (X) on firm value (Y) is 44.2% and the remaining 55.8% is influenced by other variables. Keywords: Financial Performance, Firm Value